2021
DOI: 10.3390/diagnostics11040714
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment [18F]FDG PET/CT Prognostic Factors in Patients with Squamous Cell Cervical Carcinoma FIGO IIIC1

Abstract: Purpose: This study aims to determine whether semiquantitative parameters obtained from both the primary tumor and metastatic pelvic lymph nodes (PLN) diagnosed in fluoro-18-deoxy-glucose positron emission tomography (FDG-PET-CT) are associated with disease-free survival (DFS), local control (LC), distant metastasis-free survival (DMFS) and overall survival (OS) in patients with locally advanced squamous cervical cancer (LACC) and metastatic pelvic lymph nodes. Materials: Retrospective analysis was performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In another retrospective study G.D Di Stasio et.al revealed that SUVmax ≥10.08, MTV ≥27.89, and TLG ≥134.85 conferred a significantly worse prognosis in 49 patients with pleomorphic lung carcinoma, and that the metabolic biomarkers mentioned above could be used to predict recurrence and death [29]. Ewa Burchardt et.al, in a multivariate COX regression analysis of 93 locally advanced squamous cervical cancer patients who received radical cisplatin-based chemoradiotherapy, found that SUVmax above 12.6 and TLG above 245.7 were independent predictors of OS [30]. Lin Ching Chan et al studied 108 patients with NPC receiving chemoradiotherapy and found that a pretreatment SUV >8.35 could lead to a significantly worse 3-year OS compared to a lower SUV value.…”
Section: Discussionmentioning
confidence: 99%
“…In another retrospective study G.D Di Stasio et.al revealed that SUVmax ≥10.08, MTV ≥27.89, and TLG ≥134.85 conferred a significantly worse prognosis in 49 patients with pleomorphic lung carcinoma, and that the metabolic biomarkers mentioned above could be used to predict recurrence and death [29]. Ewa Burchardt et.al, in a multivariate COX regression analysis of 93 locally advanced squamous cervical cancer patients who received radical cisplatin-based chemoradiotherapy, found that SUVmax above 12.6 and TLG above 245.7 were independent predictors of OS [30]. Lin Ching Chan et al studied 108 patients with NPC receiving chemoradiotherapy and found that a pretreatment SUV >8.35 could lead to a significantly worse 3-year OS compared to a lower SUV value.…”
Section: Discussionmentioning
confidence: 99%
“…In another retrospective study G.D Di Stasio et.al revealed that SUVmax ≥ 10.08, MTV ≥ 27.89, and TLG ≥ 134.85 conferred a signi cantly worse prognosis in 49 patients with pleomorphic lung carcinoma, and that the metabolic biomarkers mentioned above could be used to predict recurrence and death [29]. Ewa Burchardt et.al, in a multivariate COX regression analysis of 93 locally advanced squamous cervical cancer patients who received radical cisplatin-based chemoradiotherapy, found that SUVmax above 12.6 and TLG above 245.7 were independent predictors of OS [30]. Lin Ching Chan et al studied 108 patients with NPC receiving chemoradiotherapy and found that a pretreatment SUV > 8.35 could lead to a signi cantly worse 3-year OS compared to a lower SUV value.…”
Section: Discussionmentioning
confidence: 99%